2006
DOI: 10.1111/j.1468-1331.2006.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing hemorrhagic transformation in ischemic stroke: a clinicopathological comparison

Abstract: As hemorrhagic transformation (HTr) is a frequent complication and can worsen the outcome of acute ischemic stroke, our aim was to assess the risk factors of HTr. Using the database of our neuropathological laboratory, 245 consecutive acute ischemic stroke patients were analyzed. An exploratory logistic regression procedure was carried out to find the best multiple model identifying the factors associated with HTr. The autopsy revealed ischemic infarct in 175 (71%) and ischemic infarct with HTr in 70 (29%) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 28 publications
5
46
0
1
Order By: Relevance
“…Furthermore, diagnostic possibilities are often different in the routine practice as compared to well-defined and sponsored studies which last for a particular period of time. Moreover, ischaemic stroke patients usually have days or weeks [8,19] (in our sample 11.71 days, SD 13.16) before death with reduced level of consciousness and critical medical status. Therefore, the premortal diagnosis of haemorrhagic transformations could only be possible with daily repeat CT or MRI during the critically ill period, which is not possible either from the ethical or the financial point of view.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Furthermore, diagnostic possibilities are often different in the routine practice as compared to well-defined and sponsored studies which last for a particular period of time. Moreover, ischaemic stroke patients usually have days or weeks [8,19] (in our sample 11.71 days, SD 13.16) before death with reduced level of consciousness and critical medical status. Therefore, the premortal diagnosis of haemorrhagic transformations could only be possible with daily repeat CT or MRI during the critically ill period, which is not possible either from the ethical or the financial point of view.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, the results of the clinical and neuropathological diagnostic tools are heterogenous, difficult to compare them, and the population examined can make it even more heterogenous due to the fact that autopsy results can be gained from fatal cases exclusively. Kerényi et al analysed an autopsy series of 245 patients with ischaemic stroke with haemorrhagic transformation in 29% [8]. Lodder et al reported an autopsy series with 48 patients dying within 15 days following a supratentorial cerebral infarct.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations